Faktor Risiko Penyakit Neuropati Diabetik Perifer: Sebuah Tinjauan Deskriptif pada Wanita Penderita Diabetes Melitus Tipe 2 - Sri Andriani Ibrahim; Elvie Febby Dungga; Hariadi Said (Jurnal Keperawatan Silampari, 2022)
This study aims to dissect the problem of diabetic neuropathy by analyzing risk factors such as age, length of suffering from Diabetes Mellitus (DM), history of contraceptive use, and glycemic control, which are the source of triggers. This study is a cross-sectional study with an analytical observational design. The results showed that from a sample of 225 patients with type 2 diabetes, 192 samples (85.4%) had diabetic neuropathy, while the remaining 33 samples (14.6%) did not have diabetic neuropathy. Regarding the length of suffering from DM, history of contraceptive use, and glycemic control, this study showed a significant relationship between these three variables on the incidence of diabetic neuropathy with -values ​​of 0.048, 0.044, and 0.004, respectively. On the other hand, in terms of the relationship between age and the incidence of neuropathy, this study revealed no significant relationship between the two with an -value of 0.476. In conclusion, the factors associated with diabetic neuropathy are the duration of diabetes mellitus, history of contraceptive use, and glycemic control. Keywords: Diabetes Mellitus, Risk Factors, Diabetic Neuropathy